Impact of the 2008 economic crisis on the burden of hepatitis B and C diseases in Southern European countries - Claudia Palladino; Rebeca Ramis; Ifeanyi Jude Ezeonwumelu; Antonio Biondi; Giulia Carreras; Florian Fischer; Silvano Gallus; Davide Golinelli; Giuseppe Gorini; Shoaib Hassan; Zubair Kabir; Ai Koyanagi; et al. (BMC, 2024)
Abstract Background The economic crisis that began in 2008 has severely affected Southern (Greece, Italy, Portugal, Spain) Western European (SWE) countries of Western Europe (WE) and may have affected ongoing efforts to eliminate viral hepatitis. This study was conducted to investigate the impact of the economic crisis on the burden of HBV and HCV disease. Methods Global Burden of Diseases 2019 data were used to analyse the rates of epidemiological metrics of HBV and HCV acute and chronic infections in SWE and WE. Time series modelling was performed to quantify the impact of healthcare expenditure on the time trend of HBV and HCV disease burden in 2000-2019. Results Declining trends in incidence and prevalence rates of acute HBV (aHBV) and chronic HBV were observed in SWE and WE, with the pace of decline being slower in the post-austerity period (2010-2019) and mortality due to HBV stabilised in SWE. Acute HCV (aHCV) metrics and chronic HCV incidence and mortality showed a stable trend in SWE and WE, whereas the prevalence of chronic HCV showed an oscillating trend, decreasing in WE in 2010-2019 (p < 0.001). Liver cancer due to both hepatitis infections showed a stagnant burden over time. An inverse association was observed between health expenditure and metrics of both acute and chronic HBV and HCV. Conclusions Epidemiological metrics for HBV and HCV showed a slower pace of decline in the post-austerity period with better improvement for HBV, a stabilisation of mortality and a stagnant burden for liver cancer due to both hepatitis infections. The economic crisis of 2008 had a negative impact on the burden of hepatitis B and C. Elimination of HBV and HCV by 2030 will be a major challenge in the SWE countries.